Efficacy of ketogenic diet therapy in infants with epilepsy: A systematic review and meta-analysis - Tejaputri, Nadzila Anindya; Maryam, Salsabiila; Clarisa, Dina; Amelia, Putri (Medical Faculty of Brawijaya University, Indonesia, 2023)
Introduction: The ketogenic diet therapy, a high-fat, low-carbohydrate diet, has been known since the 1920s as a therapeutic option in treating drug-resistant epilepsy. However, with the increasing incidence of the infant population, research on this subject is still limited. This systematic review and meta-analysis aimed to evaluate the efficacy of ketogenic diet therapy in infants with epilepsy. Methods: We searched the articles from Cochrane Library, Embase, Pubmed, ScienceDirect, and Scopus, based on predetermined inclusion criteria. Four investigators independently performed screening, study selection, extracted data, and assessed the quality of relevant articles. We used the Newcastle-Ottawa Quality Assessment Scale to assess the risk of bias in included articles. We present the results of the meta-analysis using a forest plot. Results: We identified 1781 studies from database screening, with eight cohort studies in this study. Our meta-analysis revealed that an estimate of 69% of infants with epilepsy achieved ≥50% seizure reduction in three months follow-up (95% confidence interval [CI] 56- 82%) and an estimate of 36% of infants achieved seizure freedom (95% confidence interval [CI] 20- 51%). Retention rates ranged from 91% at three months to 28% at 24 months. The most common side effects reported were dyslipidemia (131/355, 36.9%), gastrointestinal disturbances (66/355, 18.6%), and hyperkeratosis/acidosis (42/355, 11.8%). Conclusion: Ketogenic diet therapy is well tolerated and effectively reduces seizure frequency at three months in infants with epilepsy.